Daily Oral Administration of the Novel Androgen 11β-MNTDC Markedly Suppresses Serum Gonadotropins in Healthy Men - Yuen, Fiona; Thirumalai, Arthi; Pham, Cindy; Swerdloff, Ronald S; Anawalt, Bradley D; Liu, Peter Y; Amory, John K; Bremner, William J; Dart, Clint; Wu, Hongsheng; Hull, Laura; Blithe, Diana L; et al. (The journal of clinical endocrinology and metabolism, 2020)
Abstract Background 11β-methyl-19-nortestosterone (11β-MNT) is a modified testosterone (T) with androgenic and progestational activity. A single oral dose of the prodrug, 11β-MNT dodecylcarbonate (11β-MNTDC), was well tolerated in healthy men. Methods We conducted a randomized, double-blind study at 2 academic medical centers. 42 healthy men (18–50 years) were randomized to receive oral placebo or 11β-MNTDC, 200 or 400 mg daily, for 28 consecutive days. Primary outcome (safety and tolerability) measures were assessed twice per week. Subjects underwent serial blood sampling over 24 hours on days 1 and 28 to assess secondary outcomes: pharmacokinetics (serum drug concentrations); pharmacodynamics of 11β-MNTDC (serum sex steroids and gonadotropins); and mood and sexual function (via validated questionnaires). Results There were no serious adverse events. No participants discontinued because of an adverse event or laboratory test abnormality. 11β-MNTDC resulted in a dose-related increase in serum 11β-MNTDC and 11β-MNT concentrations sustained over 24 hours. Administration of 11β-MNTDC resulted in a marked suppression of serum gonadotropins, T, calculated free T, estradiol, and SHBG over the treatment period (P < 0.01). Adverse effects that may be related to 11β-MNTDC included weight gain, acne, headaches, fatigue, and mild mood changes, with 5 men reporting decreased libido and 3 decreased erectile/ejaculatory function. Serum low-density lipoprotein cholesterol, weight (~2 kg), hematocrit, and hemoglobin increased and serum high-density lipoprotein cholesterol decreased in both 11β-MNTDC groups. Conclusion Daily oral 11β-MNTDC for 28 days in healthy men markedly suppressed serum gonadotropin and T concentrations without serious adverse effects. These results warrant further evaluation of 11β-MNTDC as a potential male oral contraceptive.